Manajemen Kawasan Tanpa Rokok Berbasis Pendidikan Islam di Perguruan Tinggi - Wildan Nur Hidayat; Sabillah Nur Fadillah Fadillah; Shidik Wahidun Alqomar Alqomar; Nia Muthoharoh Muthoharoh; Dalima Septiria Septiria (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to analyze the management of Smoke-Free Areas (KTR) based on Islamic educational values at UIN Fatmawati Sukarno Bengkulu as an effort to build a healthy, orderly, and sustainable academic environment. The research approach uses a descriptive qualitative method through interviews, observations, and document studies involving campus leaders, lecturers, the Green Campus implementation team, and participants in the Ecotheology and Curriculum of Love Socialization and Workshop activities. The results of the study indicate that institutional readiness is supported by formal regulations, a clear organizational structure, leadership commitment, and collaborative networks between campus units and external parties. The impact of implementing KTR includes an increase in a more disciplined academic culture, a healthier learning environment, reinforcement of religious values, and the growth of ecological awareness among the academic community. However, its implementation still faces challenges such as resistance from some students, limited supporting facilities, lack of socialization, and inconsistency in supervision. This study emphasizes that the success of smoke-free areas (KTR) in Islamic universities depends on the integration of health values, institutional governance, and character education, making it a relevant and sustainable model for implementing a Green Campus.